Dynamic Behaviors of Fiber-Reinforced Cellular Concrete Fabricated with Millimeter-Sized Superabsorbent Polymer - Junru Ren; Ling Zhou; Chaoshan Yang; Rui Mu; Lei Mao; Yuhao Zhu (Advances in Civil Engineering)
A novel cellular concrete with millimeter-level pores fabricated with superabsorbent polymers and fiber is introduced. Porous structure with reinforcement of fiber are adopted to improve crack resistance and shock-absorbing ability. To investigate the dynamic mechanical performance of fiber-reinforced cellular concrete, quasistatic compression and split Hopkinson pressure bar tests with strain rate from 15 to 90 s−1 were conducted. Three different fiber volume fractions (0.2%, 0.6%, and 1%), and two types of fibers (polypropylene fiber and basalt fiber (BF)) were adopted. Along with two levels of porosities (20% and 60%), total of 12 mix designs of cellular concrete to three-level axial impacting. The research results show that the novel cellular concrete is sensitive to high strain rates, demonstrating increasing dynamic compressive strength, dynamic elastic modulus, dynamic increase factor (DIF), and peak toughness with the increase in strain rate. In addition to the inertia effect, the locally enhanced porous structure and fiber structure can change the stress field and crack path, along with the energy consumption of deformation and cracks in the pores. The amount of fiber, physicochemical property, distribution, and shape amplify or dampen through its thickening effect, interface reaction, and stress transmission. Recommended fiber types and dosages were proposed to improve strength, stiffness, and toughness. BF showed an enhanced performance in terms of strength, modulus, and sharp strain-rate effect. Rules of DIFs were also studied. Awareness of the dynamic properties provides a foundation for proper design of structural members and increases the use of cellular concrete.